ERRATUM TO: THE DETERMINANTS IN THE MANAGEMENT OF PREGNANCIES COMPLICATED WITH IMMUNE THROMBOCYTOPENIA (İstanbul Tıp Fakültesi Dergisi)
Çiğdem KUNT İŞGÜDER, Tuğba SARAÇ SİVRİKOZ, Mehtap AKIN, Törehan ASLAN, Lütfiye SELÇUK UYGUR, Şule BİROL İNCE, İbrahim KALELİOGLU, Sevgi BEŞIŞIK, Recep HAS, Alkan YILDIRIMIn the article by Kunt İşgüder et al., titled ‘The Determinants in the Management of Pregnancies Complicated with Immune Thrombocytopenia’ published in the October 2023 issue of the Journal of İstanbul Faculty of Medicine, an error was inadvertently made in the authors’ institutional information. After evaluating the situation with the editor and technical office, the following information has been added to the PDF file.